Profile of mecasermin for the long-term treatment of growth failure in children and adolescents with severe primary IGF-1 deficiency - Danilo Fintini; Claudia Brufani; Marco Cappa (Dove Medical Press, 2009)
Danilo Fintini, Claudia Brufani, Marco CappaEndocrinology Unit, “Bambino Gesù” Children’s Hospital-IRCCS, Rome, ItalyAbstract: Growth hormone insensitivity syndrome (GHI) or insulin-like growth factor-1 (IGF-1) deficiency (IGFD) is characterized by deficit of IGF-1 production due to alteration of response of growth hormone (GH) receptor to GH. This syndrome is due to mutation of GH receptor or IGF-1 gene and patients affected showed no response to GH therapy. The only treatment is recombinant IGF-1 (mecasermin), which has been available since 1986, but approved in the United States by the US Food and Drug Administration only in 2005 and in Europe by the European Medicines Agency in 2007. To date, few studies are available on long-term treatment with mecasermin in IGFD patients and some of them have a very small number of subjects. In this review we discuss briefly clinical features of severe primary IGFD, laboratory findings, and indications for treatment. Results of long-term therapy with rhIGF1 (mecasermin) in patients affected by severe primary IGFD and possible side effects are explained.Keywords: mecasermin, therapy, Laron syndrome, IGF-1